Elaboración del reglamento para el laboratorio de interpretación turística para la carrera de ingeniería en ecoturismo de la UA-CAREN de la Universidad Técnica de Cotopaxi - Cunuhay Chusin, Freddy Mauricio (2014)
The present researching has a purpose the creation to a Tourist Interpretation Home Lab Regulations in the Ecotourism Engineer Career in the Technical University of Cotopaxi in Latacunga Canton, Cotopaxi province, This regulations will be an important tool that helps to control the work inside camping and recreation, simulation and buildings areas, directed to get a good service and the correct use for teachers, students and the public people. The first chapter is based in all of the real information obtained in different data bases in school, high-school, this information is used to legalize the work, with the Romano Rights analyses because of the rules have a Romano origin, after that it permits to study the origin and evolution to the rules that start with the French Revolution, so that with the legal frame and the main categories….